Microbial culture vs. mNGS: diagnostic variations in periprosthetic joint infection - Lin, Lan; Li, Xiaolin; Li, Jiayu; Wu, Baijian; Lin, Yiming; Li, Wenbo; Li, Hongyan; Guo, Yufeng; Huang, Chengguo; Huang, Zida; Zhang, Wenming; Fang, Xinyu (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aimed to compare the diagnostic performance of conventional microbial culture and metagenomic next-generation sequencing (mNGS) in detecting pathogens in periprosthetic joint infection (PJI) and to identify factors contributing to discrepancies between these two methods.MethodsA total of 167 patients with suspected PJI (including PJI patients and aseptic failure patients) who underwent revision joint replacement at our center from September 2017 to April 2024 were enrolled. Demographic data, prior antibiotic use, and results of microbial culture and mNGS were documented. Joint fluid, periprosthetic tissue, or prosthetic ultrasonic fluid samples were collected, and at least one sample from each patient underwent both microbial culture and mNGS testing. In the light of the concordance between culture and mNGS results, patients were divided into the detection consistent and detection inconsistent groups. The differences in pathogen detection between the two models were compared, and factors contributing to discordant results were analyzed.ResultsThe prior antibiotic use (OR = 2.137, 95% CI = 1.069-4.272, P = 0.032), polymicrobial infections (OR = 3.245, 95% CI = 1.278-8.243, P = 0.013), infection caused by rare pathogens (OR = 2.735, 95% CI = 1.129-6.627, P = 0.026), and intraoperative tissue specimens (OR = 2.837, 95% CI = 1.007-7.994, P = 0.049) were identified as risk factors for discordance between microbial culture and mNGS results, particularly in cases with negative microbial culture but positive mNGS findings. Conversely, consistency in specimen type (OR = 0.471, 95%CI=0.254-0.875, P = 0.017) was identified as a protective factor against discordance.ConclusionClinicians should optimize diagnostic strategies by tailoring microbial culture methods to the patient’s clinical condition and integrating mNGS testing where appropriate. It is recommended to use tissue specimens from the same anatomical site across multiple tests while sampling from different regions when necessary. Although this approach may increase costs, it significantly enhances the accuracy of pathogen identification and facilitates more effective treatment.